2015
DOI: 10.1016/j.cmet.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Lipid Synthesis Regulates Inflammation by Sustaining Neutrophil Membrane Phospholipid Composition and Viability

Abstract: SUMMARY Fatty acid synthase (FAS) is altered in metabolic disorders and cancer. Conventional FAS null mice die in utero so effects of whole body inhibition of lipogenesis following development are unknown. Inducible global knockout of FAS (iFASKO) in mice was lethal due to a disrupted intestinal barrier and leukopenia. Conditional loss of FAS was associated with the selective suppression of granulopoiesis without disrupting granulocytic differentiation. Transplantation of iFASKO bone marrow into wild type mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 54 publications
1
81
0
Order By: Relevance
“…We recently reported that PexRAP expression was decreased in multiple tissues of tamoxifen-treated PexRAP-iKO mice, including liver, bone marrow, and white adipose tissue, but not in the brain. Adult PexRAP-iKO mice treated with tamoxifen survive but have leukopenia due to the nearly complete loss of neutrophils (Lodhi et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that PexRAP expression was decreased in multiple tissues of tamoxifen-treated PexRAP-iKO mice, including liver, bone marrow, and white adipose tissue, but not in the brain. Adult PexRAP-iKO mice treated with tamoxifen survive but have leukopenia due to the nearly complete loss of neutrophils (Lodhi et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Generation of tamoxifen-inducible global PexRAP knockout (PexRAP-iKO) mice has been previously described (Lodhi et al, 2015). To induce knockout, ten to twelve week-old control (PexRAP lox/lox without Cre) and PexRAP-iKO (PexRAP lox/lox /Rosa-CreER) mice were treated daily with tamoxifen (50 μg/g body weight) for 5 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Given the shared roles in ROS and lipid metabolism between the two organelles, we speculate that MAVS recruitment to mitochondrial and peroxisomal membranes could be related to lipid and/or ROS metabolism. Indeed peroxisomal lipid synthesis can regulate immune cells as highlighted by the recent finding that loss of PexRAP, a peroxisomal enzyme required for ether lipid synthesis, results in neutropenia (Lodhi et al, 2015). …”
Section: Mitochondrial Signaling Is Necessary For Responses To Activamentioning
confidence: 99%
“…The gene encoding the enzyme that catalyzes the terminal peroxisomal step was recently identified, and the protein was named peroxisomal reductase activating peroxisome proliferator-activated receptor γ (PexRAP), based on its proposed function in adipocytes [14]. Ether lipids account for up to 20% of the total phospholipid content in humans and are particularly abundant in the brain, heart, and neutrophils [15]. Plasmalogens are important components of cellular membranes and may be involved in the organization of cholesterol-rich membrane regions known as detergent-resistant microdomains, which have been implicated in cellular signaling [16].…”
Section: Major Metabolic Functions Of Peroxisomesmentioning
confidence: 99%